EFEKTIVITAS KONSELING KELOMPOK TEKNIK BEHAVIOR CONTRACT UNTUK MENINGKATKAN DISIPLIN SISWA KELAS VIII MTS NEGERI 2 PONTIANAK - Yunda Andari, Putri; Putri, Amallia; Yanti, Elli (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to examine the effectiveness of group counseling using the Behavior Contract technique in improving the discipline of eighth-grade students at MTs Negeri 2 Pontianak. The study employed an experimental method with a pre-experimental design, specifically a one-group pretest–posttest design. The sample was selected using a purposive sampling technique, consisting of seven students who exhibited the lowest levels of discipline based on records of tardiness and rule violations among eighth-grade students.The results indicated that the mean pretest score of students’ discipline was 42, which was categorized as low, while the posttest mean score increased to 65, categorized as high. Statistical analysis using the paired-samples t-test revealed a significance value of 0.004 (p < 0.05), indicating a statistically significant difference between students’ discipline levels before and after the intervention.These findings suggest that the application of the Behavior Contract technique is effective in improving students’ discipline, particularly in terms of attendance and compliance with school dress regulations. Therefore, it can be concluded that group counseling using the Behavior Contract technique is effective in enhancing the discipline of eighth-grade students at MTs Negeri 2 Pontianak.